Oxford Anthology of the Brazilian Short Story. - Jackson, K.David (Oxford University Press, 2006)
Contains a selection of short stories by the best-known authors in Brazilian literature, from the late nineteenth century. This anthology concludes with a haunting story, set in the opera theater in Manaus by one of Brazil's most successful writers, Milton Hatoum.